Process for producing cellulosic material with improved dehydration
By heat-treating MFC suspensions or wet webs, the problem of poor dewatering behavior of MFC materials in the prior art is solved, achieving faster dewatering speeds and improved drainage properties.
Patent Information
- Application Number
- CN202380046918.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively improve dehydration behavior when producing films and barrier papers containing microfibrillated cellulose (MFC), resulting in increased drainage resistance.
By performing the MFC suspension or wet material for at least once, it is at least once, especially after removing the small level of the MFC and concentrating it, which is heated, which significantly improves the dehydration speed of the MFC film or coating.
This method significantly improves the dehydration speed of the MFC film or coating, and improves drainage performance without changing the color or sensory properties of the fiber material.
Smart Images

Figure BDA0005186360900000101 
Figure BDA0005186360900000111
Abstract
Description
Technical Field
[0001] The present invention relates to a process for producing a cellulosic material having improved dewatering behavior. The cellulosic material produced according to the invention can be used, for example, in the preparation of films and coatings. Background Art
[0002] Films and barrier papers containing large amounts of microfibrillated cellulose (MFC) are known in the art. Depending on how they are produced, the films can have particularly advantageous strength and / or barrier properties while being biodegradable and renewable. Films containing MFC are used, for example, in the manufacture of packaging materials and can be laminated or provided on the surface of a paper or paperboard material.
[0003] One of the advantages of MFC is its ability to hold water. Unfortunately, it is also one of the disadvantages when making films or barriers or using it in paperboard manufacturing. Many solutions have been proposed to improve drainage, such as reduced pH of the MFC suspension, enzymatic treatment of the MFC to remove hemicellulose, or fractionation of the MFC.
[0004] The prior art document further teaches that, in particular when the fibers are derivatized (i.e. chemically modified) before fibrillation, the obtained fibril suspension provides a membrane with improved barrier properties, in particular to gases. Therefore, when preparing a fibril suspension, it is advantageous if the suspension contains a larger amount of individual fibrils and is substantially free of fibers. Another way to visualize the degree of fibrillation or the residue of larger fiber fragments or coarse fibers is to determine the transparency of the suspension or, for example, the water retention value (WRV), which generally increases (the turbidity decreases, the water retention (i.e. the water holding capacity) increases).
[0005] Although it is clear that a higher content of fibrils having nanometer size will provide better barrier properties, it is obvious that it negatively affects drainage resistance, which is an important step in forming a barrier layer.
[0006] WO2021116988A1 teaches the use of keratinized particles from MFC. Different approaches to dry MFC are presented.
[0007] US2021395949A1 relates to a fractionation method for MFC in order to produce nanocellulose with better uniformity in nanofibril size distribution. The invention discloses the option of returning the fibers to, for example, the first or second defibrillation step.
[0008] US2019316293A1 relates to a method for fractionating a suspension of a blend containing cellulose nanofilaments or cellulose microfilaments, such as by a dilution-fractionation step. The method may include a washing step before the fractionation step, wherein the washing may be performed at high pH or low pH. The document also teaches that the removal of the finest fraction has a positive effect on tensile strength, but the document does not mention the effect on dewatering / drainage resistance and barrier properties.
[0009] Larsson A et al. (Cellulose, 26 (2019), 1565-1575: fractionation of MFC to optimize dewatering time when making films by filtration) teach the effect of fractionation of MFC made from bleached sulfite pulp on, for example, filtration time and mechanical properties of the obtained sheets. Both filtration-based and centrifugation-based techniques were used. With increasing concentration of fine MFC, strength properties were obtained. However, the document emphasizes that there is a significant loss of material during fractionation.
[0010] US9809655B2 relates to modified nanofibril cellulose and reducing the viscosity of the suspension. In one embodiment, the suspension is subjected to a heat treatment in the range of 90-180°C and most preferably 120-140°C, which reduces the zero shear viscosity. The applicant further claims that it was found that the heat treatment destroyed the remaining fiber fragments and changed the gel structure, and the size of the fibrils remained unchanged. Summary of the invention
[0011] Surprisingly, it has been found that the dewatering rate of MFC during the preparation of MFC films or coatings can be significantly improved if an MFC suspension or a wet web formed from the suspension is subjected to at least one heat treatment. Particularly surprising effects are obtained if a small fraction (fines) of MFC is first removed and then the MFC is concentrated and then subjected to a heat treatment.
[0012] The present invention therefore relates to a method for preparing a treated fibrous material in the form of a suspension or a wet web, the method comprising the following steps:
[0013] a) providing a suspension comprising MFC or highly refined pulp, wherein the MFC or highly refined pulp is at least 50% of the solids of the suspension, and wherein the suspension has a dewatering resistance in the range of from 72 to 99 SR° measured as a Schopper-Riegler (SR) value according to EN ISO 5267-1;
[0014] b) removing from the suspension 2 to 25% by weight of solids, wherein the content of platelet-like fine material having a length of less than 0.2 mm in the removed fraction is at least 50%, determined as a percentage of the projected area of all measured objects in the removed fraction using a Valmet FiberImage Analyzer (FS5);
[0015] c) adjusting the solids content of the suspension from step b) to at least 2% solids content by weight;
[0016] d) subjecting the cellulosic material in the suspension from step c) to a heat treatment step, wherein the cellulosic material in the suspension is subjected to a temperature in the range from 50 to 150° C. for at least 10 seconds to obtain a treated cellulosic material, wherein the heat treatment is performed on the suspension and / or on a wet web formed from said suspension.
[0017] Therefore, one aspect of the present invention is a treated cellulosic material obtainable according to the process of the present invention.
[0018] The invention also relates to the preparation of films or coatings or paper or paperboard, wherein the treated pulp obtained according to the invention is optionally diluted and subsequently used for the preparation of films or coatings or paper or paperboard according to methods known in the art.
[0019] Thus, one aspect of the present invention is a film or coating or paper or paperboard produced using the treated pulp according to the invention. DETAILED DESCRIPTION
[0020] The suspension in step a) comprises MFC or highly refined pulp, wherein the MFC or highly refined pulp is at least 50% of the solids of the suspension, and wherein the suspension has a Schopper Riegler (SR) value in the range of from 72 to 99 SR°, such as from 75 to 85 SR°. The Schopper-Riegler value can be determined by the standard method defined in EN ISO 5267-1.
[0021] The MFC or highly refined pulp in the suspension can be produced using methods known in the art and can be, for example, based on kraft pulp that has been refined to achieve a desired Schopper Riegler value. The pulp can also contain microfibrillated cellulose (MFC). The pulp can be a mixture of essentially unrefined pulp, low-refined pulp, slightly refined pulp, and / or medium refined pulp mixed with highly refined pulp and / or MFC. In addition to the pulp, the suspension can also contain additives typically used in papermaking.
[0022] The suspension in step a) may contain a mixture of different types of fibers, such as microfibrillated cellulose and a certain amount of other types of fibers, such as kraft fibers, fines, reinforcing fibers, synthetic fibers, dissolving pulp, TMP or CTMP, PGW, recycled fibers / pulp, etc. The hemicellulose content of the solids of the suspension in step a) is preferably less than 25 wt.-%, more preferably less than 22 wt.-%. The hemicellulose content of the solids of the suspension in step a) is preferably at least 2 wt.-%, more preferably at least 5 wt.-%.
[0023] The suspension in step a) may also contain other process or functional additives such as fillers, pigments, wet strength chemicals, retention chemicals, crosslinkers, softeners or plasticizers, adhesive primers, wetting agents, biocides, optical dyes, colorants, fluorescent brighteners, defoaming chemicals, hydrophobic chemicals such as AKD, ASA, waxes, resins, etc. In one embodiment of the present invention, the suspension in step a) does not contain internal sizing agents, cationic retention and drainage chemicals, cationic fillers or fixing agents.
[0024] The pH of the suspension in step a) is preferably in the range of from 3 to 9, such as from 4 to 8, or from 4 to 6.
[0025] The step of removing 2 to 25% by weight of solids from the suspension of step a), wherein the content of flake-like fine material having a length of less than 0.2 mm in the removed fraction is at least 50%, determined as a percentage of the projected area of all measured objects in the removed fraction, can be carried out using methods known in the art. For example, this step can be carried out using a belt washer or a washer Vario-S plit (Voith GmbH). In Vario-Split, materials such as ash and / or fines can be removed. Preferably, at least 70% of the removed solids are flaky fines material having a length of less than 0.2 mm, which is determined as a percentage of the projected area of all measured objects in the removed fraction. More preferably, at least 90% of the removed solids are flaky fines material having a length of less than 0.2 mm, which is determined as a percentage of the projected area of all measured objects in the removed fraction. The characteristics of the removed fraction can be determined using a Valmet Fiber Image Analyzer (Valmet FS5). When determined using a Valmet Fiber Image Analyzer (Valmet FS5), flaky fines material having a length of less than 0.2 mm can also be described as "fines A". For the Valmet Fiber Image Analyzer (ValmetFS5), the device version can be version 2.3 and the client version can be 1.86. For determination of the fraction discussed above, i.e. the "fines A" fraction, a Valmet fiber image analyzer (Valmet FS5) determines the percentage of projected area of measured particles having a defined length. In one embodiment, the step of removing 2 to 25 wt. % of solids from the suspension of step a) may be performed by filtration.
[0026] Preferably, from 2 to 8 wt% of solids are removed in the step of removing a fraction of solids from the suspension of step a). More preferably, from 2 to 4 wt% of solids are removed from the suspension.
[0027] The solids content of the suspension in step a) is preferably in the range from 0.1% to 1.9%, so that 1 kg of suspension preferably contains 1-19 g of solids.
[0028] The step of adjusting the solid content of the suspension of MFC or highly refined pulp to at least 2 wt% solid content can be carried out using methods known in the art, such as using a decanter or by filtration, such as filtration using a porous membrane or centrifugation or evaporation to remove liquid from the suspension. Preferably, the solid content is less than 10 wt%, such as less than 5 wt%.
[0029] The heat treatment in step d) is carried out on the suspension and / or on the wet web formed from the suspension.
[0030] In the heat treatment step, the fibrous material of the suspension is subjected to a temperature in the range of from 50 to 150° C. for at least 1 minute to obtain a treated pulp. In one embodiment, the suspension is subjected to a temperature in the range of from 60 to 130° C., such as from 70 to 95° C. The duration of the heat treatment is preferably in the range of from 1 to 60 minutes, such as from 5 to 40 minutes, or from 10 to 30 minutes. The heat treatment can be carried out using methods known in the art, for example by passing steam through the suspension. In one embodiment, the heat treatment is carried out in a pressurized chamber. It has been found that the heat treatment obtains keratinization of the fibrils or fibrillated fibers of the suspension, or parts thereof. The heat treatment can also inactivate microbial activity and enzymes, making it possible to store the intermediate product without adding an antimicrobial agent.
[0031] In one embodiment, the heat treatment of the fibrous material in the suspension is carried out on a wet web formed by the suspension. In this embodiment, the wet web is formed by providing the suspension to, for example, a porous screen or on a non-porous belt to obtain a wet web. The suspension obtained in the form of a wet web (which may have been partially dehydrated, such as by pressing) is subjected to a heat treatment, for example by exposing one or both sides of the wet web to steam or using impact drying or radiation drying, such as by using infrared radiation for drying. The solid content of the wet web at the time of the heat treatment is preferably in the range of from 5% by weight to 98% by weight, such as from 10% by weight to 50% by weight, or from 10% by weight to 40% by weight, or from 10% by weight to 30% by weight, or from 10% by weight to 20% by weight. When steam is used, the temperature of the steam is preferably in the range of from 100 to 150° C., such as from 100 to 120° C. The duration of the heat treatment is preferably in the range of from 10 seconds to 60 minutes, such as from 1 to 15 minutes. Preferably, the weight of the wet web (based on dry material) is 5-500 g / m 2 , more preferably 10-200g / m 2 , most preferably 15-150g / m 2 in the range.
[0032] Heat treatment according to the invention typically does not alter the color or organoleptic properties of the cellulosic material.
[0033] In one embodiment, the Schopper Riegler value of the heat-treated pulp obtained in step d) is at least 2 SR° less than the Schopper Riegler value of the suspension of step c).
[0034] The treated pulp obtained according to the process of the invention can be used according to methods known in the art. For example, the treated pulp can be used in the production of films or coatings or paper or board, for example using a paper machine or using casting.
[0035] The wet web of the treated pulp according to the present invention can be formed, for example, by wet laying or tape casting methods. For wet laying, the process can be carried out in a paper machine such as a fourdrinier or other forming types such as a double-end former or a hybrid former. The web can be a single-layer or multi-layer web made with one or more headboxes or a single web machine or a plurality of webs.
[0036] In the wet laying process, a suspension is prepared and provided to a porous wire mesh. Dewatering occurs through the wire mesh fabric and optionally in a subsequent pressing section. Drying is usually done using convection (cylinders, metal belts) or radiation drying (IR) or hot air. Typical wet laying processes are fourdrinier paper machine forming machines, for example, used in papermaking. In the tape casting process, a wet web is formed, for example, on a polymer or metal belt, and the subsequent initial dewatering is mainly carried out in one direction, such as via evaporation using various known techniques.
[0037] The dewatering and / or drying of the web is carried out so that the moisture content at the end of the dewatering and / or drying is preferably less than 50 wt. %, more preferably less than 20 wt. %, most preferably less than 10 wt. %, even more preferably less than 5 wt. %. The product obtained after the dewatering and / or drying of the web can be redispersed. After redispersion, the treated and redispersed pulp can be used in a second wet substrate forming to produce, for example, a film.
[0038] According to a further embodiment of the present invention, a laminate comprising paper, paperboard or film prepared using the treated pulp according to the present invention is provided. Such a laminate may, for example, additionally comprise a layer of a thermoplastic polymer (based on fossils or made from renewable resources), such as any of the following: polyethylene, polyvinyl alcohol, EVOH, starch (including modified starch), cellulose derivatives (methylcellulose, hydroxypropyl cellulose, etc.), hemicellulose, protein, styrene / butadiene, styrene / acrylate, acrylate (acryl) / vinyl acetate, polypropylene, polyethylene terephthalate, polyethylene furandicarboxylate, PVDC, PCL, PHA, PHB, and polylactic acid. The thermoplastic polymer layer may, for example, be provided by extrusion coating, film coating or dispersion coating. Such a laminate structure may provide superior barrier properties and may be biodegradable and / or compostable and / or repulpable. According to one embodiment of the present invention, the polyethylene may be any of the following: high-density polyethylene and low-density polyethylene, or a mixture or variant thereof that can be easily selected by a person skilled in the art. Paper, paperboard or film produced using the treated pulp according to the invention may also be part of a flexible packaging material such as a stand-alone pouch or bag, or may be incorporated into, for example, boxes, bags, packaging films, cups, containers, trays, bottles, etc.
[0039] Highly refined pulp can be made from unfractionated cellulose starting material. Highly refined pulp can also be prepared according to the method disclosed in WO2021 / 001751A. In this embodiment, the highly refined pulp is preferably produced by:
[0040] a) providing a fine fiber fraction obtained by fractionation of cellulose pulp;
[0041] b) subjecting the fine fiber fraction to refining at a consistency in the range of 0.5-30% by weight to a Schopper-Riegler (SR) value in the range of 80-98 determined according to standard ISO 5267-1, in order to obtain a highly refined pulp.
[0042] The fine fiber fraction for the preparation of highly refined pulp can be obtained, for example, by separating the cellulosic pulp starting material in a pressure screen to obtain a fraction with shorter and finer fibers. The dry weight of the fine fiber fraction can, for example, contain less than 75% by weight, less than 50% by weight, less than 25% by weight of the total dry weight of the unfractionated cellulosic pulp starting material for the preparation of highly refined pulp.
[0043] If a fine fiber fraction is used in the preparation of a highly refined pulp, it typically has an average fiber length of fibers having a length > 0.2 mm and below 1.7 mm (when determined according to ISO 16065-2) and a content of fibers having a length > 0.2 mm of at least 5 million fibers / gram, based on dry weight. The content of fibers having a length > 0.2 mm of the fine fiber fraction is typically less than 10 million fibers / gram, based on dry weight.
[0044] Microfibrillated cellulose (MFC) shall in the context of this patent application refer to cellulose particles, fibers, or fibrils having a width or diameter from 20 nm to 1000 nm.
[0045] There are various methods to make MFC, such as single or multiple pass refining, pre-hydrolysis followed by refining or high shear decomposition or release of fibrils. One or more pretreatment steps are usually required to make MFC manufacture energy efficient and sustainable at the same time. Therefore, the cellulose fibers of the pulp used in the production of MFC can be natural or enzymatically or chemically pretreated, for example to reduce the number of hemicellulose or lignin. Cellulose fibers can be chemically modified before fibrillation, wherein the cellulose molecules contain other (or more) functional groups different from those found in the original cellulose. Such groups include carboxymethyl (CM), aldehydes and / or carboxyl groups (cellulose obtained by oxidation mediated by N-oxyl, such as "TEMPO"), or quaternary ammonium (cationic cellulose). After modification or oxidation in one of the methods described above, it is easier to decompose the fibers into MFC.
[0046] MFC can also be produced from wood cellulose fibers, both hardwood and softwood fibers. It can also be made from microbial sources, agricultural fibers such as wheat straw pulp, bamboo, bagasse or other non-wood fiber sources. It can be made from pulp, including pulp from virgin fibers such as mechanical, chemical and / or thermomechanical pulp. It can also be made from broke or recycled paper.
[0047] Example
[0048] Highly fibrillated bleached kraft pulp was prepared by fibrillating bleached softwood kraft pulp at low consistency to a drainage resistance of °SR 95. The fibrillated cellulose was suspended to a consistency of ca 0.1 wt% before making the wet substrate or wet film.
[0049] The refined pulp was further subjected to fines removal by treating the sample in a DDJ (dynamic drainage tank) equipped with a 200 mesh screen, which resulted in a 14 wt% removal of fines. When the pH was adjusted to 5 before fractionation, the amount of fines consumed was 24 wt%. The removed material was analyzed using a Valmet FS5 fiber image analyzer. It was found that about 94% of the removed solid material was "fines A", i.e., flaky fine material having a length of less than 0.2 mm, which was determined as a percentage of the projected area of all measured objects in the removed fraction.
[0050] The fines A and fines B (lamellar fines, particles with a width of less than 10 μm and a length of more than 0.2 mm) values of highly fibrillated bleached kraft pulp were determined using a Valmet FS5 fiber image analyzer to be approximately 47% and 45%, respectively.
[0051] A 30 gsm film was prepared from the obtained suspension. In the following examples, the dehydration time was determined and a 30 gsm film was formed according to the following:
[0052] The MFC suspension was diluted to 0.1 wt% consistency with reverse osmosis purified water and subjected to stick mixing (30 s) and magnetic stirring (2 min). 125.6 g of the diluted and mixed suspension was poured into a filter equipped with a membrane filter ( 0.65 μm pore size). The diameter of the circular filter area is 73mm. Immediately after pouring the suspension into the funnel, turn on the vacuum and start recording the time. The dehydration time (s) recorded during filtration is the time required for all visible water to disappear from the top of the filter cake. The wet filter cake is removed from the filtration device together with the membrane filter and placed between two blotting papers. The filter cake (i.e., membrane) is then couched, wet pressed at 410kPa for 5 minutes, and dried in a drum dryer at 80°C for at least 90 minutes. The dried membrane is weighed after conditioning at 23°C / 50%RH. In order to obtain a specific dehydration value (s / g), the recorded dehydration time (s) is divided by the weight of the dried membrane ( g ). This was done four times for each sample.
[0053] Example 1 - Comparison
[0054] The highly fibrillated cellulose suspension was subjected to rod mixing (2 x 30 seconds) and dewatered on a membrane to form a wet matrix while the drainage resistance or dewatering time was recorded according to the procedure described above.
[0055] Example 2 - Comparison
[0056] In this case, a highly fibrillated cellulose suspension is subjected to a dewatering step on a membrane to form a wet substrate, which is then laid between blotting papers. The solid content after blotting is about 25-30% by weight. After laying, the wet substrate is redispersed with a rod mixer and subjected to a second dewatering. The dewatering time during the formation of the wet substrate before laying ("dewatering time 1") and the dewatering time during the second wet substrate formation after laying and redispersion ("dewatering time 2") are measured.
[0057] Example 3 - Comparison
[0058] In this case, the highly fibrillated cellulose was subjected to two dewatering steps in the same way as in Example 2, but the laying step was followed by a pressing step, which was similar to mechanical pressure dewatering with a load of about 400 kPa.
[0059] Example 4 - Comparison
[0060] In this case, the highly fibrillated cellulose was first subjected to fines removal and then to two dewatering steps in the same way as in Example 3 above, following a pressing step.
[0061] Example 5 - Comparison
[0062] The highly fibrillated cellulose was first subjected to fines removal, after which the pH of the suspension was lowered to 5 and then proceeded in a similar manner as in Example 4.
[0063] Example 6
[0064] In adjustment p H(5) and before the wet substrate is formed, the highly fibrillated cellulose is subjected to fines removal. The wet substrate is further pressed for dehydration and then subjected to steam treatment (100-120°C) for 10 minutes. The wet film is then redispersed before the second wet substrate is formed.
[0065] Example 7-Comparison
[0066] In this case, the highly fibrillated cellulose was subjected to a heat treatment (90° C., 30 min) and then to a first and a second dewatering step according to the same procedure as used in Example 3. In this experiment, no removal of fine material was performed.
[0067] Example 8 - Comparison
[0068] In this case, the highly fibrillated cellulose was subjected to fines removal and subsequently to heat treatment (90° C., 30 min) in the form of a suspension with a solids content of 0.15 wt. % and then processed as in Example 7.
[0069] Example 9
[0070] In contrast to the process steps in Example 6, pH adjustment was performed before fines removal and subsequent wet substrate formation. After the wet substrate was produced, the substrate was subjected to steam treatment (10 minutes, steam temperature 100° C.) and then processed as in Example 6.
[0071] result
[0072] Table I summarizes the effects of various treatment steps according to the present invention on dehydration or drainage resistance. When dehydration time or drainage resistance is normalized, it is clear that p The most efficient treatment was obtained when both H adjustment and fines consumption were followed by dewatering and steam treatment, which confirmed that fibrils and fiber properties were modified, which was attributed to wet keratinization. Dewatering in the second dewatering stage was significantly improved, confirming the role of both increased solids content and steam treatment in keratinization, see Example 9.
[0073] Furthermore, Sample 6 also demonstrated that removal of fines followed by pH adjustment and further steam treatment would reduce the dewatering resistance, especially in the second dewatering step.
[0074] Table I
[0075]
[0076] Table II FS5 results for wet substrates of the above examples dispersed in water
[0077]
[0078] In view of the above detailed description of the invention, other modifications and variations will become apparent to those skilled in the art. However, it should be apparent that such other modifications and variations can be implemented without departing from the spirit and scope of the invention.
Claims
1. A process for preparing a treated fibrous material in the form of a suspension or a wet web, the process comprising the following steps: a) providing a suspension comprising MFC or highly refined pulp, wherein the MFC or highly refined pulp is at least 50% of the solids of the suspension, and wherein the suspension has a dewatering resistance measured as a Schopper-Riegler (SR) value in accordance with EN ISO 5267-1 in the range from 72 to 99 SR°; b) removing from the suspension 2 to 25% by weight of solids, wherein the content of platelet-like fine material having a length of less than 0.2 mm in the removed fraction is at least 50%, determined as a percentage of the projected area of all measured objects in the removed fraction using a Valmet Fiber Image Analyzer (FS5); c) adjusting the solids content of the suspension from step b) to at least 2% solids content by weight; d) subjecting the cellulosic material in the form of a suspension from step c) to a heat treatment step, wherein the suspension is subjected to a temperature in the range from 50 to 150° C. for at least 10 seconds to obtain a treated cellulosic material, wherein the heat treatment is carried out on the suspension and / or on a wet web formed from the suspension.
2. The process according to claim 1, wherein the pH of the suspension in step a) is in the range from pH 4 to 8.
3. Process according to claim 1 or 2, wherein the duration of the heat treatment in step c) is in the range from 1 minute to 1 hour.
4. A process according to any one of claims 1 to 3 wherein the wet web is formed by tape casting onto a polymer or metal belt.
5. The process according to any one of claims 1 to 4, wherein the heat treatment is performed on a wet web.
6. The process according to claim 5, wherein dewatering and / or drying of the heat treated wet web is performed to obtain a film.
7. Treated cellulosic material obtainable by a process according to any one of claims 1 to 6.
8. A membrane obtainable according to claim 7.
9. Paper, paperboard, or film comprising the treated cellulosic material according to claim 7.
10. Packaging material comprising the paper, paperboard or film according to claim 9.
Citation Information
Patent Citations
Process for producing a nanocelullosic material comprising at least two stages of defibrillation of cellulosic feedstock and at least one intermediate fractioning stage
US20210395949A1
Method of modifying nanofibrillar cellulose composition
US9809655B2
Refined cellulose fiber composition
WO2021001751A1
Method of modifying nanofibrillar cellulose composition
CN105492689A
Method for the production of coated paper, paperbaord or film and coated paper, paperboard or film
CN110088401A